Lansoprazole inhibits the cysteine protease legumain by binding to the active site. Issue 2 (11th April 2019) - Bosnjak, Tatjana; Solberg, Rigmor; Hemati, Paya Diana; Jafari, Abbas; Kassem, Moustapha; Johansen, Harald Thidemann
Abstract: Proton pump inhibitors (PPIs) are prodrugs used in the treatment of peptic ulcer diseases. Once activated by acidic pH, the PPIs subsequently inhibit the secretion of gastric acid by covalently forming disulphide bonds with the SH groups of the parietal proton pump, that is the H + /K + ‐ATPase. Long‐term use of PPIs has been associated with numerous adverse effects, including bone fractures. Considering the mechanism of activation, PPIs could also be active in acidic micro‐environments such as in lysosomes, tumours and bone resorption sites. We suggested that the SH group in the active site of cysteine proteases could be susceptible for inhibition by PPIs. In this study, the inhibition by lansoprazole was shown on the cysteine proteases legumain and cathepsin B by incubating purified proteases or cell lysates with lansoprazole at different concentrations and pH conditions. The mechanism of legumain inhibition was shown to be a direct interaction of lansoprazole with the SH group in the active site, and thus blocking binding of the legumain‐selective activity‐based probe MP‐L01. Lansoprazole was also shown to inhibit both legumain and cathepsin B in various cell models like HEK293, monoclonal legumain over‐expressing HEK293 cells (M38L) and RAW264.7 macrophages, but not in human bone marrow‐derived skeletal (mesenchymal) stem cells (hBMSC‐TERT). During hBMSC‐TERT differentiation to osteoblasts, lansoprazole inhibited legumain secretion, alkaline phosphatase activity, but had no effects on in vitro mineralization capacity. In conclusion, lansoprazole acts as a direct covalent inhibitor of cysteine proteases via disulphide bonds with the SH group in the protease active site. Such inhibition of cysteine proteases could explain some of the off‐target effects of PPIs.